1994
DOI: 10.1002/pd.1970141007
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal confirmation of prenatally diagnosed trisomy 16 mosaicism in two phenotypically abnormal liveborns

Abstract: Two phenotypically abnormal liveborns in whom trisomy 16 mosaicism was diagnosed prenatally by amniocentesis are described. Analysis of a percutaneous umbilical blood sample in one case revealed a normal chromosomal complement. Ultrasound examinations performed at the time of amniocentesis were normal. Serial sonography during the late second and third trimesters demonstrated progressive intrauterine growth retardation (IUGR) in both fetuses and a cardiac defect in one. At birth, both infants had dysmorphic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…This case was initially identified as a result of elevated MSAFP and highly elevated hCG. A number of cases have been noted to have somewhat elevated MSAFP (Hajianpour et al, 1992;Devi et al, 1993;Rosenblum-Vos et al, 1993;Pletcher et al, 1994;Vaughan et al, 1994;Meck et al, 1995;Davies et al, 1995;Zimmermann et al, 1995) but the more striking finding in our case is the hCG value. At the University of Connecticut laboratory, in a total of 32 676 triple marker screening tests, only four had hCG exceeding 10 MOM.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This case was initially identified as a result of elevated MSAFP and highly elevated hCG. A number of cases have been noted to have somewhat elevated MSAFP (Hajianpour et al, 1992;Devi et al, 1993;Rosenblum-Vos et al, 1993;Pletcher et al, 1994;Vaughan et al, 1994;Meck et al, 1995;Davies et al, 1995;Zimmermann et al, 1995) but the more striking finding in our case is the hCG value. At the University of Connecticut laboratory, in a total of 32 676 triple marker screening tests, only four had hCG exceeding 10 MOM.…”
Section: Discussionsupporting
confidence: 50%
“…The first well-characterized case of a newborn with trisomy 16 mosaicism was described by Gilbertson in 1990 and since then, there have been at least ten other cases in which trisomy 16 mosaicism has been established on the basis of both normal and trisomy 16 cells present in newborn or fetal tissues (Table I). The main features associated with the disorder have been reviewed by Pletcher et al (1994) and include intrauterine growth retardation (IUGR), cardiac defects, and craniofacial and body asymmetry. In addition to those cases where trisomy 16 mosaicism has been confirmed in fetal tissue, there have been numerous instances where trisomy 16 has been noted during prenatal diagnostic testing and where there have been adverse pregnancy outcomes, but where confirmatory cytogenetic analyses have failed to identify trisomy 16 cells in fetal or newborn tissues (reviewed by Wolstenholme, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although cases with poorer outcome (e.g., severe growth restriction or presence of malformation) may have been more likely to be submitted for UPD testing, there should be no bias regarding the presence or absence of UPD among these cases. Data from thirty-three cases were from other published reports to date [Bennett et al, 1992;Hajianpour et al, 1992;Jalal et al, 1992;Williams et al, 1992;Lindor et al, 1993;Sutcliffe et al, 1993;Garber et al, 1994;Pletcher et al, 1994;Vaughan et al, 1994;Davies et al, 1995;Hajianpour, 1995;Whiteford et al, 1995;Zimmerman et al, 1995;Brandenburg et al, 1996;O'Riordan et al, 1996;Tantravahi et al, 1996;Hsu et al, 1997;Moore et al, 1997;Sanchez et al, 1997;Smith et al, 1997;Wang et al, 1997;Astner et al, 1998;Benn, 1998;Hsu et al, 1998;Sirchia et al, 1998;Van Opstal et al, 1998;Wang et al, 1998;Abu-Amero et al, 1999;Farra et al, 2000;Johnson et al, 2000;Van Opstal et al, 2001]. Although a large series of trisomy 16 cases was reviewed in Benn [1998], these data were verified from the original sources and care was taken to eliminate duplicated cases (e.g., Vancouver study cases published by other centers and cases published in two separate reports).…”
Section: Methodsmentioning
confidence: 97%
“…While complete trisomy 16 appears uniformly lethal, survival of infants with mosaic trisomy 16, although rare, has been documented (Greally et al, 1990;Gilbertson et al, 1990;Devi et al, 1993;Lindor et al, 1993;Garber et al, 1994;Pletcher et al, 1994;Hajianpour and Habiabian, 1995). To date, all molecular studies of parental origin of trisomy 16 have demonstrated that the extra chromosome is maternally derived.…”
Section: Introductionmentioning
confidence: 96%